2019
DOI: 10.3390/molecules24122346
|View full text |Cite
|
Sign up to set email alerts
|

High Concentrations of Polyelectrolyte Complex Nanoparticles Decrease Activity of Osteoclasts

Abstract: Fracture treatment in osteoporotic patients is still challenging. Osteoporosis emerges when there is an imbalance between bone formation and resorption in favor of resorption by osteoclasts. Thus, new implant materials for osteoporotic fracture treatment should promote bone formation and reduce bone resorption. Nanoparticles can serve as drug delivery systems for growth factors like Brain-Derived Neurotrophic Factor (BDNF), which stimulated osteoblast differentiation. Therefore, polyelectrolyte complex nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…On the contrary, BDNF also doesn’t increase the expression of OPG to inhibit osteoclastogenesis and activity of osteoclasts. We suppose that BDNF does not affect osteoclasts in cell cultures of cells from healthy individuals as recently shown [ 16 , 17 ]. The situation in samples and cells of patients with multiple myeloma and myeloma animal models is different [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…On the contrary, BDNF also doesn’t increase the expression of OPG to inhibit osteoclastogenesis and activity of osteoclasts. We suppose that BDNF does not affect osteoclasts in cell cultures of cells from healthy individuals as recently shown [ 16 , 17 ]. The situation in samples and cells of patients with multiple myeloma and myeloma animal models is different [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 54%
“…MLO-Y4 is able to proliferate as reported previously [ 23 ], but still holds the main characteristics of osteocytes [ 21 ]. Recent studies of our group have shown that the concentration of 40 ng/mL BDNF in the cell culture medium stimulated alkaline phosphatase (ALP) activity of osteoblasts and enhanced the cell number of MSC as progenitors of osteoblasts [ 9 ], whereas no alteration in the activity of osteoclasts and their differentiation was found [ 16 , 17 ]. Studies of other groups have reported positive effects with other concentrations ranging from 5 ng/mL to 100 ng/mL BDNF, and several cell types of different species to be affected when analyzed by a panel of functional assays [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations